CPX-351 in FLT3-mutated acute myeloid leukemia - Andrews, Claire; Pullarkat, Vinod; Recher, Christian (Frontiers in Oncology, 2023)
CPX-351, a dual-drug liposomal encapsulation of daunorubicin and cytarabine in a 1:5 molar ratio, is approved for the treatment of newly diagnosed therapy-related acute myeloid leukemia (AML) or AML with myelodysplasia-related changes. In a pivotal phase III trial, CPX-351 significantly improved overall survival compared with standard-of-care 7+3 chemotherapy (7 days cytarabine; 3 days daunorubicin) in adults aged 60-75 years with newly diagnosed high-risk or secondary AML (median 9.56 vs 5.95 months; hazard ratio 0.69; 95% confidence interval: 0.52-0.90; P = 0.003). Approximately 30% of patients with newly diagnosed AML have mutations in the FLT3 gene, which may be associated with poor outcomes. Here, we review the current in vitro, clinical, and real-world evidence on the use of CPX-351 in patients with AML and mutations in FLT3. Additionally, we review preliminary data from clinical trials and patient case reports that suggest the combination of CPX-351 with FLT3 inhibitors may represent another treatment option for patients with FLT3 mutation-positive AML.